‘Uzlah Practice to Enhance Santri’s Mentality and Spirituality - Zaenal Arifin; Mayashofa Rhoyachin (Jurnal Pendidikan Islam, 2019)
This article aims to investigate how santri understood the concept of ‘uzlah in Pesantren and how they participated in ‘uzlah activities to enhance their mentality and spirituality.  ‘Uzlah is a form of self-isolation and an effort to detach from everything dealing with the world. Its purpose is to get closer to Allah. The research applied Al – Ghazali framework theory to describe and elaborate students’ uzlah practice. The type of the research was qualitative applying phenomenology approach. The data collection technique were observation and focus group discussion for students to investigate their understanding on ‘uzlah practice. The data analysis process applied flow models as the followings: data reduction, data display, and conclusion. The research found that the santri understood concept of ‘uzlah as the way to perform activity and a treatment that position themselves to live with the Sufi attitude without ignoring their role as a member of society. Through the activity of ‘uzlah, santri’s spirituality and mentality were built as a form of integrity between religious activity and their factual life pattern in the society.